2009
DOI: 10.1007/s00535-009-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones increase the prevalence of Barrett’s esophagus

Abstract: The presence of gallstones was independently associated with the presence of ESEM in the Japanese outpatient population, suggesting a causal association of distal esophageal bile exposure with the development of ESEM. Further studies are needed to confirm our findings in cases with histologically confirmed Barrett's esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
2
14
1
Order By: Relevance
“…It is a premalignant lesion that is detected in a majority of patients with EAC. Gastroesophageal reflux disease (GERD) and bile reflux are known to cause BE and EAC 1. Caudal-related homologue 2 (CDX2), is a homeodomain transcription factor that regulates normal intestinal cell differentiation by functioning as a tumor suppressor protein, and its expression levels are associated with the prognosis of adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…It is a premalignant lesion that is detected in a majority of patients with EAC. Gastroesophageal reflux disease (GERD) and bile reflux are known to cause BE and EAC 1. Caudal-related homologue 2 (CDX2), is a homeodomain transcription factor that regulates normal intestinal cell differentiation by functioning as a tumor suppressor protein, and its expression levels are associated with the prognosis of adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a positive association was also observed between the presence of gastric corpus atrophy and that of BE [10]. However, several studies have shown an inverse association between the presence of gastric mucosal atrophy and of H. pylori infection and that of BE [11].…”
Section: Introductionmentioning
confidence: 82%
“…We recently conducted a case-control study and reported that the presence of gallstones was associated with an increase in the risk of BE [10]. In addition, a positive association was also observed between the presence of gastric corpus atrophy and that of BE [10].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations